Cruising the staged Wonderland: Scenographic photography and the queering of space. Issue 1 (1st December 2021) - Coyle, Sean
This article attempts to introduce and define the creative practice of 'scenographic photography' through the exploration of a body of practice-based research completed as part of a Ph.D. at the University of Tasmania in 2018. As research, it examines how traditionally representational forms of photography and scenography can inform each other through the more performative mode of 'scenographic photography', an interdisciplinary neologism operating between the performing, spatial and visual arts. Throughout this article, in attempting to define 'scenographic photography' as an emergent field, I will concurrently explore how queer space making was used as a critical tool for the research, visualization, execution and exhibiting of this body of work. The title of the body of work ‐ Cruising Wonderland ‐ refers to a specific 'beat' site in Sydney associated with illicit encounters and the homophobic violence it engendered during the 1980s, as well as an embodied means of re-presenting such traumatic histories. Within Cruising Wonderland scenographic scale-model making is adopted as a critical tool with which to interrogate specific sites of queer trauma. The inherent 'wonder' and fascination associated with the art of the miniature encourages the possibility of a reparative reading not always possible via the explicit documentary tradition of photographing actual sites of trauma. Once presented the audience are required to 'cruise' the darkened exhibition environment, like the 'beat' spaces referenced in the work, with an acute sensory awareness of their surroundings, of fellow spectators and how they, as participants within Wonderland, perform and are perceived by others. This immersive approach to engaging with the work is designed to encourage a process of empathic engagement, illuminating often-invisible histories, allowing us to move towards reparation through active re-witnessing.